Screening and Prediction of Autism in Toddlers Using SORF in Videos of Brief Family Interactions. - Huang, Huishi; Liu, Linru; You, Cong; Chen, Kaiyun; Xing, Yu; Li, Yijie; Deng, Hongzhu (Journal of Autism & Developmental Disorders, 2026)
The purpose of this study was to validate the utility of the Systematic Observation of Red Flags (SORF) for autism screening during 10-minute parent-child interactions at ages 15–24 months. A total of 54 children participated in this study, including 19 with autism spectrum disorder (ASD), 23 with developmental delay, and 12 typically developing children. Coders coded 10-minute videos of parent-child interactions based on the defined scoring criteria. The discriminative ability for outcome diagnosis was evaluated for total score, social communication score, restricted repetitive behavior score, number of red flags, and composite score. SORF scores demonstrated good discriminative ability between ASD and non-ASD children, with the composite score (AUC = 0.884) showing the best discriminative ability for outcome diagnosis and predicting likelihood of ASD in young children. The composite score represented a simplified measurement, with the cutoff score of 7 and sensitivity and specificity of 0.789 and 0.800, respectively. Significance: SORF has the potential to be used as an observational screening tool for ASD in children aged 15–24 months. The present study demonstrates the feasibility of brief observation, which may increase the practicality of SORF. Clinical Trial Registration: www.chictr.org.cn, identifier ChiCTR2100049811, 2021-08-10.